Guided Discovery Learning to Improve Students' Mathematics Representation and Collaboration at Senior High School 6 Yogyakarta - Hertanti, Retno; Azizah, Kamilah Rohadatul; Sari, Putu Purnama; Melissa, Margaretha Madha (JURNAL PENDIDIKAN MATEMATIKA, 2023)
Classroom Action Research aimed to assess the mathematical representation ability and collaboration in understanding circle material by implementing the guided discovery learning model. The data collection took place in April 2023 at SHS 6 Yogyakarta, involving 35 students from XI science. The research comprised two cycles, with a diagnostic test conducted in the first cycle focusing on the equation of a circle, particularly the position of points and lines related to the circle. In the second cycle, the diagnostic test concentrated on tangents to the circle. Data were gathered through tests, interviews, and questionnaires. The findings indicated that guided discovery learning effectively enhances both mathematical representation ability and collaboration. The average scores for the pre-cycle test were 78.87, for cycle I were 79.17, and for cycle II were 85. Moreover, the percentage of students achieving a score of 75 or higher increased from 60% in the pre-cycle to 71% in cycle I and further rose to 77% in cycle II. Regarding collaboration skills, in cycle I, 23 students were categorized as having medium-level skills, and 12 were classified as having high-level skills. In cycle II, the distribution changed with 16 students falling into the very high category, 12 in the high category, and seven in the medium category.